Effect of teleconnection patterns on cloudiness in winter in Poland - Filip, Miś (Időjárás, 2024)
The subject of the study was the effect of teleconnection patterns on cloudiness in Poland in the period 1990–2020. The analysis was conducted based on daily cloudiness values from 34 measurement stations of Institute of Meteorology and Water Management - National Research Institute and monthly North Atlantic Oscillation (NAO) and Scandinavia (SCAND) indices from the collection of Climate Prediction Center (CPC). The course of cloudiness values in winter in the multiannual period was analyzed together with its averaged spatial distrubution for the entire winter and for particular winter months. Next, the coefficient of correlation of cloudiness with a given teleconnection pattern index was calculated. The analysis also covered cloudiness in the positive and negative teleconnection phases. The results confirm a variable course and increasing trend of winter cloudiness in Poland. The average cloudiness reached 76% in the studied multiannual period. The correlation coefficient for the North Atlantic Oscillation primarily adopted negative values, and positive for the Scandinavian circulation. The strongest correlation between the teleconnection pattern and cloudiness was observed in February for NAO and in December for SCAND. Cloudiness showed no considerable differences between the positive and negative teleconnection phases.